Antineoplastic efficacy profiles of avapritinib and nintedanib in KIT D816V+ systemic mastocytosis: a preclinical study - Degenfeld-Schonburg, Lina; Gamperl, Susanne; Stefanzl, Gabriele; Schruef, Anna-Katharina; Sadovnik, Irina; Bauer, Karin; Smiljkovic, Dubravka; Eisenwort, Gregor; Peter, Barbara; Greiner, Georg; Hadzijusufovic, Emir; Schwaab, Juliana; et al. (American journal of cancer research, 2023)
Systemic mastocytosis (SM) is a hematopoietic neoplasm with a complex pathology and a variable clinical course. Clinical symptoms result from organ infiltration by mast cells (MC) and the effects of pro-inflammatory mediators released during MC activation. In SM, growth and survival of MC are triggered by various oncogenic mutant-forms of the tyrosine kinase KIT. The most prevalent variant, D816V, confers resistance against various KIT-targeting drugs, including imatinib. We examined the effects of two novel promising KIT D816V-targeting drugs, avapritinib and nintedanib, on growth, survival, and activation of neoplastic MC and compared their activity profiles with that of midostaurin. Avapritinib was found to suppress growth of HMC-1.1 cells (KIT V560G) and HMC-1.2 cells (KIT V560G + KIT D816V) with comparable IC50 values (0.1-0.25 µM). In addition, avapritinib was found to inhibit the proliferation of ROSAKIT WT cells, (IC50: 0.1-0.25 µM), ROSAKIT D816V cells (IC50: 1-5 µM), and ROSAKIT K509I cells (IC50: 0.1-0.25 µM). Nintedanib exerted even stronger growth-inhibitory effects in these cells (IC50 in HMC-1.1: 0.001-0.01 µM; HMC-1.2: 0.25-0.5 µM; ROSAKIT WT: 0.01-0.1 µM; ROSAKIT D816V: 0.5-1 µM; ROSAKIT K509I: 0.01-0.1 µM). Avapritinib and nintedanib also suppressed the growth of primary neoplastic cells in most patients with SM examined (avapritinib IC50: 0.5-5 µM; nintedanib IC50: 0.1-5 µM). Growth-inhibitory effects of avapritinib and nintedanib were accompanied by signs of apoptosis and decreased surface expression of the transferrin receptor CD71 in neoplastic MC. Finally, we were able to show that avapritinib counteracts IgE-dependent histamine secretion in basophils and MC in patients with SM. These effects of avapritinib may explain the rapid clinical improvement seen during treatment with this KIT inhibitor in patients with SM. In conclusion, avapritinib and nintedanib are new potent inhibitors of growth and survival of neoplastic MC expressing various KIT mutant forms, including D816V, V560G, and K509I, which favors the clinical development and application of these new drugs in advanced SM. Avapritinib is of particular interest as it also blocks mediator secretion in neoplastic MC.
Kein DOI vorhanden
Im Titel ist das Plus-Zeichen hochgestellt
Gesehen am 29.01.2024